1986
DOI: 10.1021/ic00232a025
|View full text |Cite
|
Sign up to set email alerts
|

Absorption spectra of d10 metal ion derivatives of plastocyanin

Abstract: Near-UV absorption studies have been carried out for various metal-replaced derivatives of spinach plastocyanin. Above 250 nm plastocyanin derivatives containing Zn(II), Cd(II), or Cu(II), as well as apoplastocyanin, exhibit very similar absorptions due to phenylalanine and tyrosine residues. In contrast, forms containing Hg(II), Cu(I), or Ag(I) show enhanced absorbance in the UV region. In difference spectra with apoplastocyanin as a reference, the Hg(II) derivative exhibits a maximum around 247 nm (Ae -9800 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…These Cu II -dependent absorption bands reappear slowly over several hours upon standing in air. Importantly, the absorption spectrum of Cu I (Cys112Asp) azurin is remarkably similar to that of the corresponding Cu I WT protein [20]; both reduced proteins show increased near-UV absorptions that can be ascribed to Cu I -centered electronic transitions [26]. In light of our finding that the copper ion is not removed by gel filtration of the [Ru II (NH 3 ) 6 ] 2c -treated Cys112Asp azurin and that the absorption spectrum of the resulting sample is very similar to that of the reduced WT protein, it is likely that Cu I remains coordinated in the Cys112Asp active site.…”
Section: Resultsmentioning
confidence: 99%
“…These Cu II -dependent absorption bands reappear slowly over several hours upon standing in air. Importantly, the absorption spectrum of Cu I (Cys112Asp) azurin is remarkably similar to that of the corresponding Cu I WT protein [20]; both reduced proteins show increased near-UV absorptions that can be ascribed to Cu I -centered electronic transitions [26]. In light of our finding that the copper ion is not removed by gel filtration of the [Ru II (NH 3 ) 6 ] 2c -treated Cys112Asp azurin and that the absorption spectrum of the resulting sample is very similar to that of the reduced WT protein, it is likely that Cu I remains coordinated in the Cys112Asp active site.…”
Section: Resultsmentioning
confidence: 99%
“…Copper removal from holo-PC and other PC-related proteins was performed as described (4). In brief, proteins were reduced by adding ascorbate and the solutions were dialyzed against 25 mM Tris/HCl buffer (pH 8.0) containing 0.01 M KCN for 2 hr at 4°C to remove the Cu+.…”
Section: Methodsmentioning
confidence: 99%
“…Assembly can be achieved in vitro simply by adding copper ion to a solution containing apo-PC (4). It has been suggested that holo-PC in chloroplasts results from chelating of copper ion by apo-PC (5) rather than from an enzyme-mediated'assembly process.…”
mentioning
confidence: 99%
“…Hg LMCT. However, low-energy charge transfer bands for two-or three-coordinate Hg(II)-thiolates and Hg(II)-thiolates with distorted tetrahedral geometry fall in the range of 230 -250 nm and 280 -310 nm respectively [6,18,19]. Hence, the significant shift in the l max is most probably due to the close proximity of two Cl ions in the solution, which might result in equilibrium between two-and four-coordinate compound.…”
Section: [Hgcl 4 ][(Nhmentioning
confidence: 99%